PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BAGIAN PROTOKOL PEMERINTAH KOTA YOGYAKARTA - Sutriyono Sutriyono (JURNAL MANAJEMEN, 2014)
This study aims to: 1). To determine the effect of motivation that carried on Improved employee performance protocol Section Yogyakarta City Government. 2). To determine the effect of employee performance on the part of Yogyakarta City Government Protocol. 3). To determine the effect of leadership style on the part of the Government of Yogyakarta City Protocol. The population in this study is an employee at the Yogyakarta city government protocol of 40 people. Samples taken are all employees of the protocol section using sampling techniques, namely Saturated samples representing the entire amount of the population. Based on the results obtained by the regression equation is: Y = 0.244X1 + 0.671X2. Based on the analysis of statistical data, indicators in this study are valid and variables are reliable. In the classic assumption test, regression models multikolonieritas free, there is no heteroscedasticity, and the normal distribution. Through the results of the calculations have been done obtained t value of 2.072 with a significance level of 0.045 is the result of less than 0.05, which means that the hypothesis in this study receive and reject Ho Ha. In this test proved statistically that work motivation has positive influence on employee performance. Through the results of the calculations have been done obtained t value of 5.694 with a significance level of 0.000 is the result of less than 0.05, which means that the hypothesis in this study receive and reject Ho Ha. In this test is statistically proven that leadership has positive inflence on employee performance. The most powerful influence on employee performance on the protocol of Yogyakarta city government leadership is a variable that is equal to 0,671. The results of this study are: 1). Motivation has positive influence on employee performance. 2). Leadership style has positive influence on employee performance. 3). Motivation and leadership styles affect the performance of employees in the city of Yogyakarta government protocol. Key words: motivation, leadership style and performance.